Analisis Semiotika Terhadap Prosesi Pernikahan Adat Jawa “Temu Manten” di Dolok Ilir I Kecamatan Dolok Batu Nanggar - Sri Nurhayati; Ahmad Fadlan; Ainul Hakim Syukri; Hassan Sazali; Maulana Andinata Maulana Andinata (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
The purpose of this study was to determine and analyze the meaning of the Javanese traditional wedding "Temu Manten" in Dolok Ilir I, Kec. Dolok Batu Nagar. This type of research uses interpretive qualitative research methods, and uses semiotic research methods, namely an analytical method to examine a sign and meaning in the object being studied based on facts in the field, namely the Javanese Traditional Wedding Procession "Temu Manten" in Dolok Ilir I, Kec. Dolok Batu Nagar. Data were collected using textbooks, references related to research. Based on the discussion and results, it is known that at the Javanese Traditional Wedding Procession "Temu Manten" in Dolok Ilir I, kec. Dolok Batu Nanggar, has a very deep meaning for the bride and groom and their families. In the procession, it can be seen that men are more in the household than women, and there are myths such as what Roland Barthes said that myths exist but do not know the truth, and in the Temu Manten procession, and in this procession the myth of Roland Barthes works that according to community belief, after carrying out the "temu manten" wedding procession, they have a harmonious, peaceful and harmonious household. But at this time for ordinary people, there are not a few who do not use this procession, because the event maker does not want to be complicated with all the existing affairs and requirements. However, there are still many people who advocate and use the Temu Manten ceremony and do not abandon the traditions that have been passed down and have been preserved, especially the people outside the island of Java.